Assisting upon entry: Helping type and approach as moderators of how role conflict affects newcomer resource drain. - Bamberger, Peter A.; Geller, Dvora; Doveh, Etti (Journal of Applied Psychology, 2017)
We extend recent research on the costs and benefits of helping to help providers by asking whether and under what conditions newcomer help giving may amplify or mitigate the role-conflict-based resource drain such individuals may experience in the context of their initial socialization. Drawing from conservation of resources (COR) theory, we propose that whether providing assistance to peers enhances or weakens newcomer help providers' resilience to such conflict-based resource drain (i.e., exhaustion) depends on both the type of help given (instrumental vs. emotional) and the orientation (more vs. less empowering) that newcomers adopt when providing it. We test our propositions on the basis of time-lagged data collected from newly hired call center representatives at the end of their first and sixth months on the job. Results largely support our predictions, with instrumental assistance mitigating, and emotional assistance exacerbating, the role-conflict-based resource drain experienced by newcomer help providers. Moreover, these amplifying effects of emotional help provision on the conflict-exhaustion relationship are largely eliminated among those newcomer help providers reporting a more empowering approach to help provision. (PsycINFO Database Record